Status of E-Commerce as Correlated to the Development of Plant Community - Cathlyn Joy N Dia; Chester Alexis C Buama; Maryjane D Fuentes; Marry Anne S Gonzales; Regina E Gloria; Noel H Natividad (Journal of Social Entrepreneurship Theory and Practice, 2023)
During the time of the pandemic in 2020, it is notable that the trend of plants flourished. However, at present, there is a decline in demand. The Municipality of Bay, Province of Laguna, is recognized as the "Garden Capital of Laguna," brimming with various plants. The local plant community represents the largest community in the Bay. Thus, the Local Government Unit of Bay acknowledges the necessity to empower and develop this plant community. This research aimed to establish a correlation between the status of e-commerce and the sustainable development of the plant community. The study utilized a descriptive research design and employed a self-made questionnaire to gather information and data from the entire population of respondents. The data collected from the survey were tallied and interpreted. The results revealed that ornamental plants significantly correlate with all the factors of sustainable development of plant communities. Furthermore, both home gardening and plant parenting showed a significant correlation with all the factors of sustainable development of plant community. Among the types of e-commerce, business-to-consumer (B2C) was the only one found to have a significant correlation with the factors of sustainable plant community development. Facebook exhibited greater significance concerning the factors of sustainable development of plant community compared to online selling websites/apps.